Adição de resíduo termofixo em matriz de polipropileno reciclado: análise de propriedades térmicas e mecânicas - Prestes Pires, Pamela Galera (Universidade Federal de São Carlos, 2017)
The proper disposal of solid waste has driven studies to enable the use of recycled materials and waste. So, in this work were molded composites using raw materials from industrial waste and evaluated several mechanical and thermal properties of composites developed. As thermoplastic matrix was used recycled polypropylene (PP) and as filler was used the residue containing thermosetting powder from high-pressure laminate manufacture process (HPL) in the proportions 10%, 14%, 20%, 30% and 40% by weight, obtaining the composites. In order to evaluate the mechanical properties of recycled PP and their composites were performed test of tensile, flexural and Charpy impact. In order to evaluate the thermal properties were performed test of softening temperature, thermal deflection temperature, dynamic-mechanical thermal analysis (DMTA), thermal behavior by differential scanning calorimetry (DSC) and degree of crystallinity. In addition, were performed analyzes of density and morphological analysis by scanning electron microscopy (SEM).The elongation, tensile and flexural strength reduced with the addition of the HPL. The flexural modulus did not change until an addition of 20%, however, the stiffness increased with 30% and 40% of HPL which contains thermosetting. The softening temperatures in relation to the recycled PP increased with the addition of 40% of the HPL. In the temperature of thermal deflection the addition of 40% of the residue caused increase when compared to the recycled PP. The presence of thermoset residue reduced tenacity of the recycled matrix from addition of 14% of HPL. The density showed increase from adding 10% of HPL. The storage modulus improved with the addition of filler. There was no change in the melting and crystallization temperature. The degree of crystallinity of recycled matrix increases with increasing amount of HPL present in the composite; and an addition of HPL showed good dispersion in the recycled PP matrix. In general, it is considered that the best results of mechanical properties (flexion and tensile) and thermal properties of composites were obtained with addition of 40% of HPL. So the use of HPL as reinforcing filler in composites is feasible and can be used for example in the manufacture of supermarket boxes, pallets, chairs, internal coating of vehicles and among others.
Addition of thermosetting residue in recycled polypropylene matrix: analysis of thermal and mechanical properties
Keywords: Compósito; Polipropileno reciclado; Resíduo de laminado; Resíduo termofixo; RLAP; Composite; Recycled polypropylene; Laminate waste; Thermosetting residue; HPL; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES